Brief history of natural sciences for nature-inspired computing in engineering - Siddique, Nazmul; Adeli, Hojjat (Journal of Civil Engineering and Management, 2016)
The goal of the authors is adroit integration of three mainstream disciplines of the natural sciences, physics, chemistry and biology to create novel problem solving paradigms. This paper presents a brief history of the development of the natural sciences and highlights some milestones which subsequently influenced many branches of science, engineering and computing as a prelude to nature-inspired computing which has captured the imagination of computing researchers in the past three decades. The idea is to summarize the massive body of knowledge in a single paper succinctly. The paper is organised into three main sections: developments in physics, developments in chemistry, and developments in biology. Examples of recently-proposed computing approaches inspired by the three branches of natural sciences are provided.